The Effect of School Principal Leadership and Teacher Work Motivation on Teacher Creativity in Seram Barat District - Yolanda Gysberthus; T. G. Ratumanan; S. Rumfot (Peneliti.net, 2022)
This study aims to determine the effect of principal leadership and teacher work motivation on the creativity of high school teachers in West Seram sub-district. The research method used in this study is a quantitative study with a correlational approach conducted on 5 high schools in West Seram sub-district with a population of 133. The sample was taken by proportional random sampling technique, and with the Slovin formula obtained a sample of 100 people. This study resulted in the following conclusions: 1) There is a positive and significant relationship between the principal's leadership on teacher creativity with an R value of 0.551, the regression line equation shows that = 75.337 + 0.350 with a tcount > ttable or 75.337 > 1.661 this is evidenced by consulting the R value with the coefficient table for the r value. other than that the regression line equation shows that = 2.381 + 0.859. 2) There is a positive and significant relationship between teacher work motivation and teacher creativity with a value of R = 0.869, forming a regression line = 28.880 + 0.749 and obtained tcount > ttable or 28,880 > 1.661. 3) Based on the significance test, the significance test was obtained with Fcount = 164.132 while Ftable with a significant level = 0.05 dk = 100 – 2 = 98 , then Ftable value = 3.938 It turns out that Fcount > Ftable or 164.132 > 3.938 then Ho rejected and H1 accepted means significant or there is an influence of principal leadership and teacher work motivation on teacher creativity.